Adsorption of rare earth elements in regolith-hosted clay deposits - Anouk M. Borst (Nature Portfolio, 2020)
Global resources of heavy Rare Earth Elements (REE) are dominantly sourced from Chinese regolith-hosted ion-adsorption deposits, yet the adsorption mechanisms remain unclear. Here, the authors find that heavy REE are adsorbed as easily leachable 8-coordinated outer-sphere hydrated complexes, dominantly onto kaolinite, in clays from both China and Madagascar.